A method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step aging.

CN122991839APending Publication Date: 2026-10-27ZHEJIANG BOTU MAGNETIC INTELLIGENT MANUFACTURING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611125082.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

这直接导致了最终磁体的剩磁(Br)和退磁曲线方形度(Hk/Hcj)出现断崖式下降

Benefits of technology

[0030]本发明克服了现有技术中低稀土(29.5% TRE)及贫硼(0.9% B)条件下烧结钕铁硼所面临的致密化困难、取向度极差、以及因晶界连续性破裂导致的矫顽力低迷这三大系统性技术偏见,突破现有技术壁垒的核心技术亮点集中体现在以下三个维度的深度交叉与协同:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991839A_ABST
    Figure CN122991839A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of magnetic material preparation technology, and discloses a method for preparing low-rare-earth, high-performance sintered NdFeB magnets based on radio frequency induction plasma micro-melting spheroidization and reverse step-ageing. The preparation method aims to overcome the performance bottleneck of traditional magnets under low-heavy rare-earth conditions through specific chemical metallurgical formulations and fluid dynamic reconstruction of the preparation process. In the early preparation stage, an extreme formulation with ultra-low PrNd and depleted B is adopted, supplemented with trace amounts of Cu, Co, Ga, Ti, and Ce for composition control. The raw materials undergo high-vacuum induction melting, rapid solidification and spinning, room-temperature hydrogen explosion, and air jet milling under high-purity nitrogen protection. This process achieves a qualitative leap in macroscopic magnetic properties, successfully reaching industry-leading levels of remanence (Br) 14.41 kGs, coercivity (Hcj) 14.13 kOe, and squareness (Hk / Hcj) as high as 95.3%, completely breaking the traditional understanding that high magnetic performance must rely on high and heavy rare-earth elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetic material preparation technology, specifically to a low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step aging, and its preparation method. Background Technology

[0002] Driven by the current global energy transition and electrification wave, high-performance sintered neodymium iron boron (Nd-Fe-B) permanent magnet materials, as the core medium for converting electrical energy into mechanical energy, are experiencing exponential growth in market demand. However, constrained by the scarcity of global rare earth resources (especially heavy rare earth elements such as Dy and Tb, and light rare earth elements such as Pr and Nd) and the drastic price fluctuations caused by mining environmental costs, how to maintain or even improve the comprehensive performance of magnets while significantly reducing the total rare earth content and completely eliminating dependence on heavy rare earths has become a pressing problem for the academic and industrial communities of permanent magnet materials.

[0003] Traditional theories of compositional design and microstructure control for sintered NdFeB magnets indicate that to obtain a dense microstructure and excellent magnetic properties, it is typically necessary to maintain a total rare earth element (TRE) content of over 30 wt.% and a sufficient boron content (B > 1.0 wt.%). During liquid-phase sintering, excess rare earth elements form a low-melting-point Nd-rich liquid phase, which plays a crucial multiple role in micro-metallurgy: firstly, it drives the rearrangement of powder particles and fills pores through capillary contraction, promoting magnet densification; secondly, it dissolves and smooths the main phase (Nd2Fe). 14 B) On the grain surface, surface defects and other antimagnetic nucleation centers are eliminated; thirdly, after cooling, a continuous nonmagnetic grain boundary phase network is formed, realizing magnetic decoupling between adjacent ferromagnetic main phase grains, thereby providing high coercivity. However, when the target product is committed to challenging the ultimate cost, compressing its formulation to an extremely low rare earth content (e.g., PrNd accounts for only 27.5%), and is in a boron-poor state (B is only 0.9%), if the traditional powder metallurgy process route (i.e., vacuum induction melting) is continued, Hydrogen explosion Airflow milling powder Magnetic field molding sintering Stepped cooling annealing will inevitably encounter the following insurmountable technical gaps and theoretical bottlenecks: First, there are bottlenecks in powder rheology and deterioration of orientation. Traditional processes for preparing single-crystal powders mainly rely on jet milling technology. Jet milling utilizes high-speed airflow to cause coarse powders after hydrogen explosion to collide and rub against each other, thereby achieving pulverization. The Nd-Fe-B powder prepared by this purely mechanical crushing method exhibits a highly irregular polygonal or gravelly morphology, with the surface covered with microcracks and sharp edges. In terms of macroscopic powder mechanics, the mechanical interlocking effect and static friction between these irregular powder particles are extremely large, resulting in a very low bulk density (usually only about 2.7 g / cm³) and extremely poor flowability (usually greater than 43 s / 50 g). In traditional rare-earth-rich formulations, due to the presence of a relatively large amount of Nd-rich phase as a natural interfacial lubricant, the powder can still undergo a certain degree of rotational alignment in the orientation magnetic field. However, in extremely low rare earth formulations, the natural lubricating phase is severely lacking. These polygonal powders are hindered from rotating in an orientation magnetic field (typically 1.5-2.5T), making it extremely difficult to overcome the enormous interparticle friction to achieve a highly consistent alignment of their easy magnetization axes (c-axis). This directly leads to a precipitous drop in the remanence (Br) and squareness (Hk / Hcj) of the final magnet.

[0004] Second, there is a contradiction between long-term sintering under extremely low liquid phase conditions and abnormal grain growth. Under the extreme condition of a PrNd content of only 27.5%, the liquid phase volume fraction in the system is at or even below the critical lower limit required for theoretical densification. To eliminate the huge porosity inside the compact and achieve complete densification of the material, traditional approaches can only force a significant increase in sintering temperature or a drastically extended sintering time. However, long-term high-temperature sintering inevitably induces severe Ostwald ripening in thermodynamics and kinetics, leading to uncontrollable abnormal growth of the main phase grains. The coarse grains are prone to multi-domain structures, and their increased specific surface area drastically increases the nucleation rate of antimagnetic nuclei, thus devastating the coercivity of the magnet. How to effectively suppress grain growth during long-term sintering in a low liquid phase is a problem that traditional formulations cannot solve independently.

[0005] Third, the failure of grain boundary phase disconnection, magnetic coupling effect, and traditional aging mechanisms. In boron-poor and low-rare-earth systems, the non-magnetic Nd2Fe grain boundary phase, originally used to isolate the ferromagnetic main phase, is extremely thin, making it prone to "disconnection" in the microstructure or the formation of discontinuous isolated islands. Adjacent Nd2Fe... 14 The strong ferromagnetic exchange coupling effect generated by the direct contact of B main phase grains makes it easy for antimagnetic domains to propagate across grain boundaries, resulting in coercivity that is difficult to meet the requirements of practical applications. In recent years, researchers have discovered that by adding elements such as Ga, Nd6Fe with antiferromagnetic or nonmagnetic characteristics can be formed at grain boundaries. 13Ga (i.e., the 6:13:1 phase) compound, the presence of which significantly improves the magnetic isolation effect of grain boundaries, enhancing coercivity and corrosion resistance. However, Nd6Fe 13 The formation conditions of the Ga phase are extremely demanding, and its stable existence temperature window is very narrow (typically around 500-560℃). In conventional step-annealing processes from high to low (e.g., direct cooling from 900℃ to 500℃), due to Nd6Fe... 13 Ga has a low nucleation rate and extremely slow atomic diffusion kinetics at low temperatures, resulting in the precipitation of Nd6Fe. 13 Ga typically exists only as isolated, blocky islands at triple junctions, unable to undergo lateral spreading along the main phase grain surface to form a continuous, fully encapsulated isolation layer. Therefore, relying on traditional heat treatment processes to excite Nd6Fe in low-rare-earth systems... 13 The continuous distribution of Ga phases to enhance coercivity faces a theoretical bottleneck that is difficult to overcome.

[0006] In summary, existing powder preparation methods and conventional heat treatment processes are completely inadequate at the levels of microscopic physics, mechanics, phase transition thermodynamics, and rheology to support the development of high-performance sintered NdFeB magnets with a low rare earth boron-poor formulation system containing only 29.5% total rare earth elements and extremely compressed purity ratios. Summary of the Invention

[0007] Based on an in-depth analysis of the physical morphological defects of powders produced by traditional air-jet milling, the hysteresis law of low-rare-earth liquid-phase solidification, and the thermodynamic barriers of grain boundary phase transitions, this invention proposes a disruptive, cross-technology, comprehensive innovative NdFeB and its preparation process. Specifically, it proposes a method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-ageing. The core objective of this invention is to provide a novel microstructure engineering and phase transition-driven manufacturing process. This process achieves a qualitative leap in macroscopic magnetic properties, successfully reaching industry-leading levels of remanence (Br) of 14.41 kGs, coercivity (Hcj) of 14.13 kOe, and squareness (Hk / Hcj) of 95.3%, completely breaking the traditional understanding that high magnetic properties must rely on high and heavy rare-earth elements.

[0008] To achieve the objectives of this invention, the method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging comprises the following steps: Step A: Batching and Melting Weigh the raw materials according to the following mass percentages: PrNd 24-27%, B 0.8-1.0%, Cu 0.1-0.3%, Co 0.4-0.6%, Ga 0.1-0.3%, Ti 0.05-0.15%, Ce 3-5%, balance Fe; The raw materials are heated and melted under vacuum and argon protection, and then rapidly solidified and poured onto a water-cooled copper roller to produce alloy castings. Step B: Hydrogen Explosion and Airflow Milling The cooled castings are loaded into a hydrogen absorption furnace for hydrogen explosion, followed by dehydrogenation treatment. Finally, the dehydrogenated powder is placed in a high-purity nitrogen atmosphere for air jet milling to prepare air jet mill coarse powder. Step C: Plasma Equipment Parameter Setting and Gas Inlet Control. Turn on the stepless radio frequency induction plasma system, set the power to 13-28 kW, and the operating frequency to 3.5-4.5 MHz; introduce multiple gases: control the flow rate of the central carrier gas (5N high-purity argon) at 8-12 slpm, the flow rate of the main working gas (5N high-purity argon) at 28-32 slpm, and the flow rate of the outermost confinement protective gas (Ar-He mixture) at 30-50 slpm. Step D: Powder Injection and Extreme Quenching Collection The coarse powder from the air jet mill is loaded into a powder feeder with vibration assistance and precise weighing feedback. It is then axially injected into the heated zone of the plasma torch thermal jet through the central carrier gas for micro-melting. After micro-melting, the powder passes through the tail flame zone and falls directly into the water-cooled extreme cold chamber with a large flow of cold air for rapid quenching, and the spheroidized powder is collected. Step E: Magnetic field orientation and cold isostatic pressing The collected spheroidized powder is transferred into a nitrogen-protected glove box, and the powder is loaded into a closed-circuit mold. Orientation molding is performed under DC or pulsed external magnetic field. Subsequently, the green body is subjected to cold isostatic pressing (CIP) densification treatment. Step F: Main Sintering The cold isostatically pressed green body is placed in a vacuum sintering furnace or a pure inert atmosphere furnace, heated to 1045-1065℃, and held for heat treatment. Step G: First-stage cooling and homogenization After the main sintering is completed, the furnace is vacuum cooled or filled with an appropriate amount of argon gas to cool down to 890-910℃ and then held at that temperature. Step H: Cryogenic Low Temperature Insulation Turn on the forced cooling system to cool down to room temperature as quickly as possible, then heat to 500-520℃ and hold for heat preservation. Step I: Reverse heating aging and furnace cooling After completing the cryogenic ultra-low temperature insulation, start the heating equipment to raise the temperature in reverse to 630-650℃, hold for 2-4 hours, and after the aging is completed, introduce a large flow of cold air to quickly cool the furnace temperature to room temperature before unloading.

[0009] Further, in step A, the raw materials are weighed according to the following mass percentages: PrNd 25.2-26.2%, B 0.8-1.0%, Cu 0.15-0.25%, Co 0.45-0.55%, Ga 0.15-0.25%, Ti 0.07-0.13%, Ce 3.5-4.5%, balance Fe.

[0010] Further, in step A, the raw materials are weighed according to the following mass percentages: PrNd 25.5-25.9%, B 0.85-0.95%, Cu 0.18-22%, Co 0.48-52%, Ga 0.18-22%, Ti 0.09-0.11%, Ce 3.8-4.2%, with the balance being Fe.

[0011] Further, in step A, the raw materials are placed in a vacuum induction melting furnace and heated to 1400-1500℃ under argon protection to melt.

[0012] Furthermore, in step A, after the raw material is melted, it is cast onto a water-cooled copper roller using a rapid solidification and casting process to obtain an alloy casting sheet with a thickness of 0.2-0.4 mm.

[0013] Furthermore, in step B, hydrogen explosion is performed at room temperature and a hydrogen pressure of 0.1-0.3 MPa.

[0014] Furthermore, in step B, dehydrogenation is performed under vacuum at 500-600°C.

[0015] Furthermore, the average particle size (D50) of the coarse powder produced by air jet milling in step B is 3-5 µm.

[0016] Furthermore, in step C, the power supply is set to 14.5-25.5 kW and the operating frequency is set to 3.8-4.2 MHz.

[0017] Furthermore, in step C, the power supply is set to 24.5-25.5 kW and the operating frequency is set to 3.9-4.1 MHz.

[0018] Furthermore, in step C, the central carrier gas flow rate is controlled at 9.5-10.5 slpm, and the main working gas flow rate is controlled at 29-31 slpm.

[0019] Furthermore, in step D, the powder feeding rate is controlled at 30-50 g / min in the powder feeder.

[0020] Furthermore, in step E, the oxygen and water content in the nitrogen-protected glove box are both controlled to be less than 50 ppm.

[0021] Furthermore, in step E, the orientation pressing is performed under a DC or pulsed external magnetic field of 2.0-2.5 T.

[0022] Furthermore, in step E, the green billet is subjected to cold isostatic pressing (CIP) densification treatment under hydraulic pressure of 200-250 MPa.

[0023] Furthermore, the vacuum degree of the vacuum sintering furnace in step F is less than 10. - ³ Pa.

[0024] Furthermore, in step F, the temperature is increased at a rate of 4-6 °C / min.

[0025] Furthermore, in step F, the temperature is raised to 1050-1060℃ and held for 5-7 hours.

[0026] Furthermore, in step G, the temperature is lowered to 895-905℃ and kept at that temperature for 2-4 hours.

[0027] Furthermore, in step H, the temperature is lowered to 505-515℃ and maintained for 5-6 hours.

[0028] Furthermore, in step I, the temperature is raised in reverse to 635-645℃ and held for 2.5-3.5 hours.

[0029] Furthermore, in step I, the temperature is raised in reverse to 639-641℃ and held for 2.5-3.5 hours.

[0030] This invention overcomes the three major systemic technical biases faced by existing technologies in sintering NdFeB under low rare earth (29.5% TRE) and boron-poor (0.9% B) conditions: difficulties in densification, extremely poor orientation, and low coercivity due to grain boundary continuity fractures. The core technical highlights that break through the existing technical barriers are concentrated in the deep cross-fertilization and synergy of the following three dimensions: Highlight 1: Cross-disciplinary introduction of radio frequency induced plasma (RF-ICP) micro-melting spheroidization technology to reshape powder rheology and surface thermodynamics This invention abandons the traditional fine-tuning of air jet mill parameters within the framework of powder metallurgy. Instead, it creatively introduces RF induction plasma spheroidization, a core technology in additive manufacturing (3D printing) and the preparation of high-end refractory metal powders, into the easily oxidized Nd-Fe-B rare earth permanent magnet powder preparation stage. By precisely controlling the hydrodynamics and extremely high temperature gradient of the electrodeless RF plasma torch, irregular polygonal air jet milled powder undergoes instantaneous surface micro-melting within milliseconds of passing through the plasma core region. Driven by liquid surface tension, the particles are instantly reconstructed into perfect spheres with minimal specific surface area, completely eliminating mechanical interlocking friction between particles. This allows the powder to exhibit ultra-high fluidity and rotational freedom like a fluid in the orientation magnetic field, directly overcoming the physical bottleneck of poor orientation in low rare earth formulations.

[0031] More importantly, plasma treatment is accompanied by extreme quenching rates (up to 10). 4 - 10 5 The K / s ratio interrupts the long-range ordering process of atomic crystallization on the powder surface, forming an "amorphous shell" with extremely high metastable state and topological disorder on the surface of spherical particles. This high-free-energy amorphous defect region provides an excellent heterogeneous nucleation site for subsequent low-temperature phase transitions, transforming the traditional understanding of "amorphous defects leading to magnetic dilution" into a "catalytic engine promoting favorable phase formation".

[0032] Highlight 2: Achieving Zener Pinning Effect During Long-Term Sintering by Utilizing Microalloying and Spheroidization Stacking Characteristics To address the contradiction that the stringent long-term sintering (1055℃ × 6h) required for densification of low rare-earth systems inevitably leads to abnormal grain growth, this invention cleverly utilizes the preferential in-situ capture reaction of trace amounts of Titanium (Ti, 0.15%) in the formulation under prolonged high temperatures. Thermodynamically, Ti atoms have a very strong chemical affinity for the extremely limited number of B atoms in the boron-poor system, preferentially binding and precipitating a hexagonal TiB2 nanophase with high melting point, high hardness, and high chemical stability. Due to the extremely high initial packing density of the spherical powder shortening the diffusion path, these in-situ generated TiB2 nanoparticles are uniformly anchored at smooth spherical grain boundaries and triangular grain boundaries, producing an extremely strong Zener pinning effect. These nano-anchors micromechanically lock the migration dynamics of the grain boundaries, perfectly suppressing Oswald ripening under 6 hours of high-temperature baking. This allows the magnet to achieve ultra-high density while maintaining a fine and uniform grain size, completely eliminating the backlash of large grains on coercivity.

[0033] Highlight 3: Pioneering a reverse step-aging mechanism based on surface amorphous induction and low-viscosity liquid phase assistance, characterized by nucleation-extension. This invention completely overturns the "step-down cooling annealing" paradigm held as the gold standard in the permanent magnet field. Targeting the unique "surface amorphization and high free energy state" of the powder after plasma spheroidization and the customized "boron-poor-Ti-Ga-Cu-containing" composite formula, it has tailored an unconventional 510℃ annealing process. Reverse heat treatment curve at 640℃.

[0034] First, by utilizing the extreme undercooling of 510℃ and the high Gibbs free energy of the amorphous shell, the nucleation barrier is greatly reduced, inducing nonferromagnetic Nd6Fe. 13 The Ga phase undergoes explosive heterogeneous nucleation at the extremely boron-depleted grain boundaries. Secondly, a novel approach is employed: by reversing the temperature to 640℃, the melting point reduction effect of the trace Cu (0.2%) in the formulation is activated. The trace Cu-rich, low-viscosity liquid phase generated during the reheating process acts as a highly efficient surfactant, carrying isolated Nd6Fe... 13 Ga-shaped core islands undergo rapid lateral spreading and fusion along extremely smooth and angular spherical main phase grain boundaries. Ultimately, this deep synergy between "physical preparation and reconstruction" and "chemical reverse evolution" weaves a continuous, dense, and extremely thin non-magnetic isolation network around each ferromagnetic grain, completely achieving magnetic decoupling between grains and squeezing out an ultra-high coercivity of 14.13 kOe under the extreme condition of no heavy rare earth elements. Attached Figure Description

[0035] Figure 1 This is a schematic diagram of the radio frequency inductively coupled plasma (RF-ICP) powder micro-melting spheroidization system of the present invention; Figure 2 This is a diagram showing the grain boundary evolution and TiB2 Zener pinning mechanism during the high-temperature long-time sintering process of the preparation method of this invention; Figure 3 This is a microscopic evolution diagram of magnetic decoupling during the reverse step aging process in the preparation method of this invention. Detailed Implementation

[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. Additional aspects and advantages of this invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. It should be understood that the following description is merely illustrative and not intended to limit the invention.

[0037] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1 to 5” is disclosed, the described range should be interpreted as including the ranges “1 to 4”, “1 to 3”, “1 to 2”, “1 to 2 and 4 to 5”, “1 to 3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.

[0038] Furthermore, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., described below refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms are not necessarily directed at the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.

[0039] The core of this invention, based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging for low-rare-earth, high-performance sintered NdFeB, lies in introducing electrodeless radio frequency induction plasma (RF-ICP) to spatially reconstruct micron-sized powder in three dimensions. The precursor coarse powder is fed into a plasma torch at a strictly constant rate. Under an Ar-He mixed protective gas atmosphere with extremely high thermal conductivity, the powder particles instantly absorb a large amount of enthalpy and undergo micro-melting contraction. They then immediately fall into a high-flow-rate water-cooled ultra-cold chamber, undergoing rapid quenching that breaks through conventional thermodynamic limits. This process not only reshapes the powder into near-perfect spheres, significantly optimizing its loose packing density and Hall flow rate, but more importantly, it freezes a highly metastable amorphous shell layer on the outermost layer of the powder.

[0040] In the subsequent forming and heat treatment stages, the spheroidized powder with excellent hydrodynamic properties achieves near-frictionless c-axis parallel orientation under a closed-circuit mold and a high-intensity magnetic field. After densification by cold isostatic pressing (CIP), a green compact is formed. The green compact is then subjected to unconventional synergistic phase transformation sintering and reverse step aging in a high-vacuum environment: during the main sintering period at 1055℃, the high-melting-point compounds precipitated in situ strongly pin the grain boundaries to inhibit the growth of the main phase grains; then, the system undergoes extreme cryogenic treatment (510℃), cleverly utilizing the amorphous shell layer remaining from the previous plasma spheroidization as a high-energy catalytic site to induce a large-scale explosive heterogeneous nucleation of the nonferromagnetic isolating phase at extremely low temperatures.

[0041] Finally, the process employs an unconventional "reverse heating" to 640°C, utilizing a melting depressant to reliquefy localized micro-regions. Driven by the liquid fluid and its excellent wettability, the isolated nucleated isolating phase undergoes omnidirectional lateral extension along smooth spherical grain boundaries, ultimately weaving into a continuous and extremely thin isolating network that completely encapsulates and decouples the main phase grains. The effectiveness of the entire invention and the quality of the final product will be verified through the standard funnel method to examine the powder's hydrodynamic properties, the closed-circuit demagnetization curve to test macroscopic remanence and intrinsic coercivity, and high-resolution transmission electron microscopy (HRTEM) and energy dispersive spectroscopy (EDS) to verify the nanoscale amorphous shell and trace element distribution, thus forming a complete technological closed loop from powder preparation and microscopic reconstruction to performance testing.

[0042] The main effects of this process are reflected in: Microfluidic Reconstruction and Ultimate Orientation: Perfectly spherical powder treated with radio frequency plasma (RF-ICP) completely transforms the high-resistance mechanical interlocking of traditional irregular powders into near-frictionless "point-to-point" contact. In the orientation magnetic field, these spherical particles rotate freely like a low-viscosity fluid, achieving a near 100% perfect parallel alignment of the single-crystal easy magnetization axis without hindrance. This fundamentally eliminates orientation deviation, resulting in a historic breakthrough in the squareness of the demagnetization curve, exceeding 95%, and remanence approaching the theoretical limit.

[0043] Long-term densification and in-situ Zener pinning: Facing the challenge of densification in liquid-deficient systems, this invention boldly employs a main sintering process at 1055℃ for up to 6 hours. To combat the resulting grain coarsening, trace amounts of Ti pre-embedded in the formulation precisely capture free B elements, precipitating a large amount of high-melting-point TiB2 nanoparticles at the triple grain boundaries. These particles act like countless sturdy anchors, using a powerful Zener pinning effect to firmly lock the migration dynamics of the grain boundaries, uniformly and tightly compressing the main phase grains within an extremely fine range of 5-8 µm, thus stabilizing the fundamental coercivity.

[0044] Reverse Stepped Aging and Interface Spreading Decoupling: Completely overturning the industry convention of "gradual cooling," the process is tailored to a reverse phase transition mechanism of "first cryogenic induction of nucleation, then warming to drive spread." First, extreme supercooling to 510℃ is used, utilizing the "amorphous shell" remaining on the powder surface as a high-energy catalyst to induce non-magnetic Nd6Fe at boron-poor grain boundaries. 13The Ga phase undergoes explosive, isolated nucleation; subsequently, an anomalous heating to 640°C is used to re-transform the local boundaries into a low-viscosity liquid phase using trace amounts of Cu. Utilizing perfect interfacial wettability, the liquid phase carries these isolated non-magnetic nuclei, rapidly extending laterally along the smooth, spherical main phase surface, ultimately weaving together a continuous, extremely thin three-dimensional isolation network that completely decouples the ferromagnetic grains, forcing out ultra-high coercivity from the microscopic level.

[0045] Example 1 Step 1 (Ingredient Preparation and Belt Spinning): Weigh the raw materials, with the following mass percentages: PrNd 25.7%, B 0.9%, Cu 0.2%, Co 0.5%, Ga 0.2%, Ti 0.1%, Ce 4%, and the remainder Fe. Place the raw materials under a vacuum of 10... - The metal is melted in an induction furnace at 3 Pa and poured onto a water-cooled copper roller at a surface linear velocity of 2-3 m / s to form a 0.3 mm thick sheet ingot.

[0046] Step 2 (Hydrogen Crushing and Powdering): The ingot is placed in a hydrogen absorption furnace, and hydrogen gas at 0.15 MPa is introduced for hydrogen absorption and explosion. Then, it is dehydrogenated under vacuum at 550℃. The dehydrogenated coarse powder is fed into an air jet mill with closed-loop nitrogen circulation. The classifier speed is set to 4000 rpm to produce irregular coarse powder with a D50 of 3.8 µm.

[0047] Step 3 (Plasma Micro-melting and Spheroidization): Coarse powder is loaded into the powder feeder and injected into the radio frequency induction plasma chamber at a constant rate of 40 g / min. The radio frequency generator power is set to 25 kW and the frequency to 4 MHz. The multi-gas settings are: central carrier gas 10 slpm Ar, main working gas 30 slpm Ar, and outermost protective gas is an Ar-He mixture containing 10% He by volume. After micro-melting, the powder falls into the bottom water-cooling chamber for cooling (cooling rate >10). 4 K / s) and collect.

[0048] Step 4 (Compression Molding): The collected powder is transferred to a glove box with an oxygen content of <10 ppm. Orientation pressing is performed under a 2.5 T pulsed magnetic field, followed by cold isostatic pressing to create a dense green body.

[0049] Step 5 (Long-time sintering): The green blank is sent into a high-vacuum sintering furnace and heated to 1055℃ at a rate of 5℃ / min, and held for 6 hours.

[0050] Step 6 (Reverse Step Aging): The furnace is vacuum cooled to 900°C and held for 3 hours; rapid air cooling is started to quickly reduce the furnace temperature to room temperature, and then it is reheated to 510°C and held for 5.5 hours; after the holding period, the temperature is not reduced, and the heating is started directly to raise the temperature to 640°C in reverse order and held for 3 hours; finally, argon gas is forcibly introduced to rapidly quench the furnace to room temperature before removing it from the furnace.

[0051] Example 2 Steps 1-2: Same as in Example 1 (ingredient preparation, belt spinning, hydrogen crushing and air jet milling).

[0052] Step 3 (Plasma Micro-Spheroidization - Parameter Adjustment): Increase the powder feed rate to 50 g / min. Reduce the RF generator power to 15 kW, maintaining the frequency at 4 MHz. Gas parameters and cooling collection method are the same as in Example 1.

[0053] Steps 4-6: Same as Example 1 (press molding, long-term sintering at 1055℃, reverse step aging at 900℃-510℃-640℃).

[0054] Example 3 Steps 1-5: Same as in Example 1 (ingredient preparation, powder making, 25 kW plasma spheroidization, pressing and molding, long-term sintering at 1055℃).

[0055] Step 6 (Reverse Step Aging - Parameter Adjustment): Reheat to 900℃ and hold for 3 hours; start rapid air cooling to 510℃ and hold for 5.5 hours; after holding, start reverse heating to 635℃ and hold for 3 hours; finally, force argon gas to rapidly quench to room temperature before removing from the furnace.

[0056] Comparative Example 1 (Traditional preparation route: despheroidization + conventional annealing) Steps 1-2: Same as in Example 1 (ingredient preparation, belt spinning, hydrogen crushing and air jet milling to prepare irregular coarse powder with D50 of 3.8 µm).

[0057] Step 3 (Skip Spheroidization): The coarse powder is not subjected to radio frequency plasma micro-spheroidization treatment.

[0058] Steps 4-5: Same as Example 1 (pressed in a glove box under an oxygen content of <10 ppm, and sintered in a furnace at 1055℃ for 6 hours).

[0059] Step 6 (Conventional Annealing): Cool the sintered body in the furnace to 900℃ and hold for 3 hours; then allow it to cool linearly to 510℃ and hold for 5.5 hours; after holding, turn off the heating and allow it to cool to room temperature in the furnace. (No reverse heating step) Comparative Example 2 (possesses spheroidizing physical properties and is annealed using conventional methods) Steps 1-5: Same as Example 1 (using the same ingredients, powder preparation, 25 kW plasma micro-melting spheroidization, pressing and shaping and long-term sintering at 1055℃).

[0060] Step 6 (Conventional Annealing): Heat the sintered body to 900℃ and hold for 3 hours; then linearly and naturally cool to 510℃ and hold for 5.5 hours; after holding, turn off the heating and allow it to cool to room temperature in the furnace. (No reverse heating step) Comparative Example 3 (Extreme process forcibly applied to conventional formula) Step 1 (Modifying Batching and Casing): Weigh the raw materials, remove Ti and Cu, and add the corresponding mass to Fe. The mass percentage is changed to: PrNd 25.7%, B 0.9%, Co 0.5%, Ga 0.2%, Ce 4%, with the remainder being Fe. Prepare ingots according to the smelting and casting process of Example 1.

[0061] Steps 2-6: exactly the same as in Example 1 (hydrogen-jet milling, 25 kW plasma micro-melting spheroidization, pressing, long-term sintering at 1055℃, and reverse step aging at 900℃-510℃-640℃).

[0062] The product performance obtained from the above embodiments and comparative examples is shown in the table below: Those skilled in the art will readily understand that the above description is merely a partial example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging, characterized in that, The preparation method includes the following steps: Step A: Batching and Melting Weigh the raw materials according to the following mass percentages: PrNd 24-27%, B 0.8-1.0%, Cu 0.1-0.3%, Co 0.4-0.6%, Ga 0.1-0.3%, Ti 0.05-0.15%, Ce 3-5%, balance Fe; The raw materials are heated and melted under vacuum and argon protection, and then rapidly solidified and poured onto a water-cooled copper roller to produce alloy castings. Step B: Hydrogen Explosion and Airflow Milling The cooled castings are loaded into a hydrogen absorption furnace for hydrogen explosion, followed by dehydrogenation treatment. Finally, the dehydrogenated powder is placed in a high-purity nitrogen atmosphere for air jet milling to prepare air jet mill coarse powder. Step C: Plasma Equipment Parameter Setting and Gas Inlet Control. Turn on the stepless radio frequency induction plasma system, set the power to 13-28 kW, and the operating frequency to 3.5-4.5 MHz; introduce multiple gases: control the central carrier gas flow rate at 8-12 slpm, the main working gas flow rate at 28-32 slpm, and the outermost confinement protection gas flow rate at 30-50 slpm. Step D: Powder Injection and Extreme Quenching Collection The coarse powder from the air jet mill is loaded into a powder feeder with vibration assistance and precise weighing feedback. It is then axially injected into the heated zone of the plasma torch thermal jet through the central carrier gas for micro-melting. After micro-melting, the powder passes through the tail flame zone and falls directly into the water-cooled extreme cold chamber with a large flow of cold air for rapid quenching, and the spheroidized powder is collected. Step E: Magnetic field orientation and cold isostatic pressing The collected spheroidized powder is transferred into a nitrogen-protected glove box, and the powder is loaded into a closed-circuit mold. Orientation pressing is performed under DC or pulsed external magnetic field. Subsequently, the green body is subjected to cold isostatic pressing densification treatment. Step F: Main Sintering The cold isostatically pressed green body is placed in a vacuum sintering furnace or a pure inert atmosphere furnace, heated to 1045-1065℃, and held for heat treatment. Step G: First-stage cooling and homogenization After the main sintering is completed, the furnace is vacuum cooled or filled with an appropriate amount of argon gas to cool down to 890-910℃ and then held at that temperature. Step H: Cryogenic Low Temperature Insulation Turn on the forced cooling system to cool down to room temperature as quickly as possible, then heat to 500-520℃ and hold for heat preservation. Step I: Reverse heating aging and furnace cooling After completing the cryogenic ultra-low temperature insulation, the heating equipment is started to raise the temperature in reverse to 630-650℃, and then the temperature is maintained. After that, a large flow of cold air is introduced to quickly cool the furnace temperature to room temperature before the furnace is unloaded.

2. The method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging according to claim 1, characterized in that, In step A, the raw materials are weighed according to the following mass percentages: PrNd 25.2-26.2%, B 0.8-1.0%, Cu 0.15-0.25%, Co 0.45-0.55%, Ga 0.15-0.25%, Ti 0.07-0.13%, Ce 3.5-4.5%, balance Fe; Preferably, in step A, the raw materials are weighed according to the following mass percentages: PrNd 25.5-25.9%, B 0.85-0.95%, Cu 0.18-22%, Co 0.48-52%, Ga 0.18-22%, Ti 0.09-0.11%, Ce 3.8-4.2%, with the balance being Fe.

3. The method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging according to claim 1, characterized in that, In step A, the raw material is placed in a vacuum induction melting furnace and heated to 1400-1500℃ under argon protection to melt. Preferably, after the raw material is melted in step A, it is cast onto a water-cooled copper roller through a rapid solidification and casting process to obtain an alloy casting sheet with a thickness of 0.2-0.4 mm.

4. The method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging according to claim 1, characterized in that, In step B, hydrogen explosion is performed at room temperature and a hydrogen pressure of 0.1-0.3 MPa; preferably, in step B, dehydrogenation is performed under vacuum at 500-600℃; preferably, the average particle size (D50) of the coarse powder produced by air jet milling in step B is 3-5 µm.

5. The method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging according to claim 1, characterized in that, In step C, the power supply is set to 14.5-25.5 kW and the operating frequency is set to 3.8-4.2 MHz; preferably, in step C, the power supply is set to 24.5-25.5 kW and the operating frequency is set to 3.9-4.1 MHz; preferably, in step C, the central carrier gas flow rate is controlled at 9.5-10.5 slpm and the main working gas flow rate is controlled at 29-31 slpm; preferably, in step D, the powder feeding rate is controlled at 30-50 g / min.

6. The method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging according to claim 1, characterized in that, In step E, the oxygen and water content in the nitrogen-protected glove box are both controlled to be less than 50 ppm; preferably, in step E, the orientation pressing is performed under a DC or pulsed external magnetic field of 2.0-2.5 T; preferably, in step E, the green blank is subjected to cold isostatic pressing densification treatment under hydraulic pressure of 200-250 MPa.

7. The method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging according to claim 1, characterized in that, In step F, the vacuum degree of the vacuum sintering furnace is less than 10. - ³ Pa; preferably, the temperature in step F is increased at a rate of 4-6 °C / min; preferably, the temperature in step F is increased to 1050-1060 °C and held for 5-7 hours.

8. The method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging according to claim 1, characterized in that, In step G, the temperature is lowered to 895-905℃ and kept at that temperature for 2-4 hours; preferably, in step H, the temperature is lowered to 505-515℃ and kept at that temperature for 5-6 hours.

9. The method for preparing low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step-aging according to claim 1, characterized in that, In step I, the temperature is raised to 635-645℃ in the reverse direction and held for 2.5-3.5 hours; preferably, in step I, the temperature is raised to 639-641℃ in the reverse direction and held for 2.5-3.5 hours.

10. The low-rare-earth, high-performance sintered NdFeB based on radio frequency induction plasma micro-melting spheroidization and reverse step aging prepared by the preparation method according to any one of claims 1-9.